Motor timing is shared between limbs during symmetric bimanual movements - Atsushi Takagi; Kazuaki Honda (iScience)
Summary: The brain activity during bimanual movements exhibits a unique pattern not seen when either arm is moved alone. Existing theories suggest that the distinct pattern may come from the integration of motor timing between the hemispheres, but specifically how they combine remains unclear. Here, we measured the muscle activation timing of the left and right shoulders during a unimanual and bimanual periodic force control task and compared the empirical results with the predictions from three competing models of motor timing integration. Our results are most consistent with the view that the motor timing of the dominant hemisphere can be shared to improve the non-dominant arm’s motor timing by up to 20%. However, the sharing of motor timing occurs more readily during symmetric bimanual movements relative to antisymmetric movements. Our results highlight the unique neural processes underlying symmetric coordination and clarify the circumstances in which motor timing can be shared between the limbs.